Assessment of nutritional status of oncology patients at hospital admission: a Portuguese real-world study - Trabulo, Carolina (2022)
Background: Nutritional status in patients with cancer has a determining role in the evolution of the disease and tolerance to treatments. Severity of undernutrition impacts morbidity and mortality in cancer patients and can limit patient response to the optimal therapies if nutritional issues are not appropriately addressed and managed. Despite the importance of malnutrition for the clinical evolution of oncology patients, there is not yet a universally accepted standard method for evaluating malnutrition in such patients. The aim of this study was to stratify the nutritional status of inpatients at an Oncology Department. Methods: This is an observational study with 561 cancer patients, assessed at admission to a Medical Oncology Department from November 2016 to February 2020. All patients were considered eligible. Non-compliant and/or comatose patients were excluded. Nutritional status was assessed using the PG-SGA, BMI classified with the WHO criteria, and calculation of the percentage of weight loss in the previous 3–6 months. Results: A total of 561 patients (303 F: 258 M; mean age 65 ± 13 years) were included. One-third of the patients, n=191/561 (34%), lost 6% of their weight in the month prior to admission and 297/561 (53%) patients lost 10.2% of weight in the previous 6 months. Mean BMI was 24.1 ± 5.8 kg/m2; N = 280/561 (50%) patients had regular BMI according to the WHO criteria. N = 331/561 (59%) patients reported eating less in the month prior to admission. N = 303/561 (54%) had moderate/severe deficits of muscle and adipose compartments. The PG-SGA identified 499/561 (89%) patients as moderately/severely malnourished, of which 466/561 (83%) patients scored ≥9 points, meeting criteria for a critical need for nutritional support. Fifteen percent of patients scored >4 points, indicating a need for directed therapy for symptom control and only 1% scored <2 points (maintenance nutritional counseling). Conclusion: In this oncological setting, a higher proportion of patients were nutritionally-at-risk or with moderate/severe malnutrition. The large majority of patients in this study presented with a critical need for nutritional intervention. These findings highlight the need for an integrated assessment of nutritional status at patient referral. This will allow early and timely nutrition care, which is recommended to prevent or reverse further deterioration of the condition and to optimize treatment administration.